Social Media and Issue Framing: How Pramono Anung Utilized Instagram as a Political Campaign Tool in The 2024 Jakarta Elections? - Ladopurap, Nourman Syahril; Kusumojati, Kisandani Priyambodo; Irwansyah, Irwansyah (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik USB YPKP, 2025)
This research examines Pramono Anung's Instagram (@pramonoanungw) campaign strategy during Jakarta's gubernatorial election (August-November 2024). Using mixed methods, the study analyzes social media content characteristics and issue framing techniques. Findings reveal dominance of personalization content, followed by information, mobilization, and interaction elements. Pramono's strategy emphasized building a visionary image through social issues advocacy, family values, and sustainability commitments, positioning him as an approachable, community-responsive leader. This research contributes to understanding social media's role in contemporary political campaigning within Jakarta's electoral context.